Feeding and oral hygiene habits of children attending daycare centres in Bangalore and their caretakers oral health knowledge, attitude and practices - S Vinay; N Naveen; N Naganandini (Wolters Kluwer Medknow Publications, 2011)
Aim: Caretakers in day-care centers play a significant role in imparting good oral hygiene practices and also extend a working relationship with parents with regard to their children's oral health. As a result of this, caregiver's dental knowledge, attitudes, beliefs and practices affect the child's oral condition. Settings and Design: A descriptive cross-sectional study involved caretakers working in day-care centers of Bangalore. Fifty-two day-care centers were randomly selected from the different zones of Bangalore city, from which 246 caretakers provided consent for participation. Materials and Methods: A comprehensive, closed-ended, self-administered questionnaire was employed which was designed to collect the sociodemographic details and to evaluate the oral health knowledge, attitudes, practice of caretakers. The institutional review committee approved the study. Data were entered using SPSS 13.01. Results: Seventy-nine percent of the subjects had good knowledge of child's tooth eruption time, clinical presentation of dental caries and the role of fluoride in caries prevention. Yet, half of the subjects found routine dental examination after all the milk teeth have erupted in the oral cavity insignificant and 41% strongly agreed that dentist should be consulted only when the child has a toothache. In spite of the good knowledge, 77% preferred to use pacifier dipped in honey/sugar if the children acted troublesome. Analogous to this, 45% gave milk/juice with sugar before the child's nap time. Conclusions: The results of this study indicate that caretaker's attitude toward oral health care needs is far from acceptable standards to mirror any positive impact on the children.